2018
DOI: 10.1002/2017jb014973
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Alteration of Pyrite to Pyrrhotite During Earthquakes: New Evidence of Seismic Slip in the Rock Record

Abstract: Seismic slip zones convey important information on earthquake energy dissipation and rupture processes. However, geological records of earthquakes along exhumed faults remain scarce. They can be traced with a variety of methods that establish the frictional heating of seismic slip, although each has certain assets and disadvantages. Here we describe a mineral magnetic method to identify seismic slip along with its peak temperature through examination of magnetic mineral assemblages within a fault zone in deep‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 94 publications
(129 reference statements)
2
42
0
Order By: Relevance
“…The lower E a allows the decomposition or reaction of minerals to occur at relatively low temperatures (Hirono et al, ; Masumoto et al, ). This favors the release of iron ion from Fe‐bearing minerals, and thus the neoformation of ferrimagnetic minerals (i.e., magnetite, maghemite, and pyrrhotite) in slip zones (e.g., Chou, Song, Aubourg, Lee, et al, ; Chou, Song, Aubourg, Song, et al, ; Hirono et al, ; Pei et al, ; Tanikawa et al, ; Yang et al, , , and references therein), as also demonstrated by the present HVF experiments. These newly formed ferrimagnetic minerals, which would carry either a stable thermochemical or even a thermoremanent magnetization (Chou, Song, Aubourg, Lee, et al, ; Yang et al, ), could generally remain stable over geological times.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The lower E a allows the decomposition or reaction of minerals to occur at relatively low temperatures (Hirono et al, ; Masumoto et al, ). This favors the release of iron ion from Fe‐bearing minerals, and thus the neoformation of ferrimagnetic minerals (i.e., magnetite, maghemite, and pyrrhotite) in slip zones (e.g., Chou, Song, Aubourg, Lee, et al, ; Chou, Song, Aubourg, Song, et al, ; Hirono et al, ; Pei et al, ; Tanikawa et al, ; Yang et al, , , and references therein), as also demonstrated by the present HVF experiments. These newly formed ferrimagnetic minerals, which would carry either a stable thermochemical or even a thermoremanent magnetization (Chou, Song, Aubourg, Lee, et al, ; Yang et al, ), could generally remain stable over geological times.…”
Section: Discussionsupporting
confidence: 74%
“…This mixing limits our understanding of the intricacies of thermal transformations induced by frictional heating. Such transformations have been reported to occur pervasively in seismic slip zones (e.g., Chou, Song, Aubourg, Song, et al, ; Han et al, ; Tanikawa et al, ; Yang et al, , ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We use these concentrations to calculate the n-alkane parameters used in the analysis (Supplementary Data 2). The CPI is calculated by dividing the summed concentrations of odd chain-length n-alkanes by the summed concentrations of even chain-length n-alkanes between chain lengths of 26-35 (ΣC odd,27-35 /ΣC even, [26][27][28][29][30][31][32][33][34] ). The ADI, defined by Rabinowitz et al 33 , is calculated as (C 27 + C 31 )/(C 28 + C 29 + C 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additional evidence of frictional heating in the JFAST core samples comes from other faults identified at depths around 697, 720, and 801 mbsf. Using mineral magnetic methods, electron microscopy, and X-ray spectroscopy, Yang et al (2018) identified the presence of pyrrholite, a mildly magnetic iron sulfide mineral, exclusively within these faults zones. Ruling out other potential mechanisms for pyrrholite formation at this site, such as prolonged diagenetic reaction of magnetite or thermochemical sulfate reduction, they interpret their analyses as evidence of thermally driven pyrite-to-pyrrholite reactions at temperatures between 640°C and 800°C.…”
Section: Tōhoku-oki Fault Zone Frictional Heat Measuredmentioning
confidence: 99%